Palabras propias (Open textbook library.)
The goal of this project is to provide high-quality, accessible primary sources to those teaching and studying the histories and cultures of the Spanish-speaking world and the indigenous peoples of Latin America. Our modules cover a wide range of topics, but all consist of the same essential parts: A brief introduction that provides socio-historical context for the primary document. The text itself, often glossed for improved comprehension by non-native speakers of Spanish. A set of activities that range from comprehension to analysis, from using new vocabulary to answering creative writing and essay prompts.